Technical efficiency of agriculture in EU countries - Rusielik, Robert (Array, 2020)
The study attempts to assess the technical efficiency of agriculture in European Union countries. Two methods were used for this purpose. One was to establish a ranking and separate typological groups of countries similar to each other in terms of technical efficiency of agriculture, using the Hellwig’s taxonomic measure of development. The second one concerned the measurement of technical efficiency of EU countries using the DEA (Data Envelopment Analysis) method. A set of 6 variables determining the technology of agricultural activity was adopted for the model. The model assuming the variable effects of the BCC scale was adopted for the study. Based on the variables adopted for the DEA model, a set of diagnostic indicators was defined, which finally included 5 indicators. Based on these indicators, by means of a linear ordering method based on a synthetic variable, countries were grouped into 4 groups bringing together countries from the lowest to the highest efficiency. The results of both methods overlap in the part concerning the countries with the best efficiency. In other groups there are slight discrepancies that may result from limited access to information and selection of variables for research.